The Old Testament speaks ; v. 6 God's Word for a former generation explained for today's people - Fleming, Donald C. (Kowloon, Hong Kong Living Books for All, 1982)
Contents : v. 6 : Job, Proverbs, Ecclesiastes, Song of Solomon.
Brethren writer. Donated by the author.
Keywords: Bible. O.T. -- introductions